Postural control and functional ankle stability in professional and amateur skateboarders - Ou, Y.-K.; Chen, Z.-W.; Yeh, C.-N. (healthcare, 2021)
Basic maneuvers in skateboarding, such as the ollie, put the player at high risk for ankle injuries because of the position of the feet required to perform the maneuvers. This study investigated ankle stability and reaction time for the tibialis anterior, fibularis longus, and fibularis brevis in professional and amateur skateboarders. In total, 16 professional and 16 amateur skateboarders were recruited as participants and underwent range of motion assessments, balance testing, and muscle reaction time measurements. The results revealed that professional skateboarders had a significantly smaller inversion angle compared to amateur players, which suggested better joint control and hence greater safety in the former. Balance testing results indicated better balance in professional skateboarders, and healthy skateboarders had better balance than did injured professional and amateur skateboarders. No significant difference in muscle reaction time was observed between amateur and professional skateboarders.